Proposta de modelo para implantação da gestão por processos: um estudo na Força Aérea Brasileira - Magarão, Aline Hortale (2021)
Process management in the public sector is a topic that is constantly being addressed in the scientific community. In theoretical discourse, it is about the dissemination of good practices from the private sector for application in the public sector. However, due to the complexity in the administration of public services, obstacles that hinder the implementation of concepts, methods and tools have been observed. Over time, some programs were created with the aim of guiding public agents in improving efficiency in public management, but still, nowadays, it is not possible to consider them as a consolidated practice in the sector. As an effective action during the study, the decree 10.382/2020 that disseminates the “TransformaGov” program in order to reduce bureaucracy in the federal public system, increase the efficiency and satisfaction of users/citizens, there are several agencies that adhere to good practices, including the Ministry of Defense, to which the study's focus unit is subordinate. In this context, it is necessary to know and improve the processes of organizations in order to meet these objectives, seeking strategic alignment with the process vision, enabling the implementation of a process management model. Thus, the BPM (business process management) methodology has been a practice adopted, including in the public sector, to know, improve, automate and adapt work processes in order to support administrative and technical routines, providing greater control and quality of activities performed. However, there are obstacles for a public organization to implement BPM and align theory with practice, one of them is the hierarchical structure and constant changes in applied guidelines, in order to migrate from the functional view to the process view. Thus, this work sought to model the processes of the Administrative Secretariat (Command Section) of the Health Squadron (ES-SM), located in ALA4 located at the Santa Maria air base, which is subordinate to the Brazilian Air Force (FAB) , contributing to the adequacy of existing practices (methodologies and tools) by creating a model that was more appropriate and that would allow dissemination to other sections of the organization, thus resulting in better performance and satisfaction results for those involved in daily activities, the method adopted in the research allowed identify key variables that impact the implementation of BPM concepts, methods and tools in a public/military health organization. The study was applied using as a guide for the research limits documents such as laws, guidelines and regulations of the Institution; for data collection, a survey of the current situation (as is) of the work routines was carried out through interviews with the process executors and practical observation with subsequent validation with the head. As a result of the study, the technological product for the implementation of BPM in ES-SM was proposed, defining the roles, responsibilities, redesigning (to be) a future proposal for the most efficient flow and its respective management mechanism. The contributions permeated the scope of the development of a greater vision for processes in the administrative management of ES-SM, especially regarding the dimensions of culture, strategy and people.